Spatial data quality from process to decisions - Devillers, Rodolphe; Goodchild, H. (CRC Press, 2010)
This book provides an up-to-date overview of research being done in the field of spatial data quality, which looks at understanding, measuring, describing, and communicating information about the imperfections of geographic data used by GIS and other mapping software. It presents results from a number of current research projects in this area, from the assessment of data accuracy to legal aspects relating to the quality of geographic information.--From publisher's description.